PENGEMBANGAN VIDEO PEMBELAJARAN BERBANTU CAMTASIA STUDIO PADA MATERI PERKEMBANGAN TEKNOLOGI KELAS IV SD - Muhammad Abdul Hafizh (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
ABSTRACTThe purpose of this research is to know the feasibility of developing learning media device by using camtasia studio assisted learning video on developmental material of class IV SD. This research is research development or Research and Development, procedure in this research using steps include potential and problem, data collection, product design, design validation, design revision, product trial, product revision. Techniques of data collection using the results of observation, interviews, tests, and documentation. Data analysis technique used is dercriptif qualitative obtained from product quality questionnaire (material expert validation, media expert) in the form of quantitative data, then continued with quantitative descriptive technique using statistical test with test. The conclusions in the results of this study are the effectiveness of learning in the classroom by using camtasia studio-assisted learning videos and products worthy of use.Keywords: Media, R & D, Video